Enzymatic dispersal of dual-species biofilms carrying Listeria monocytogenes and other associated food industry bacteria. (December 2018) - Puga, C.H.; Rodríguez-López, P.; Cabo, M.L.; SanJose, C.; Orgaz, B.
Abstract: Enzyme-based treatments could therefore be used to complement regular cleaning processes. Most studies using enzymes as anti-biofilms strategy are focused on their outcome in mono-species biofilms. Nevertheless, in real environments mixed biofilms are prevalent. In this work, seven types of dual-species biofilms were selected to serve as targets for enzymatic treatments carrying different environmental strains of L. monocytogenes and accompanying bacteria isolated from dairy, meat and seafood processing plants. The effectiveness of nine commercial enzymatic preparations, including pronase, cellulase, pectinase, DNase I, lysozyme, phospholipase, peroxidase, β-glucanase and chitinase, was evaluated. For this, residual attached viable cells of both L. monocytogenes and its partners were enumerated through swabbing and colony plate counting following the action of each enzyme. Moreover, Confocal Laser Scanning Microscopy (CLSM) images were analyzed pre and after enzymatic treatments in order to quantify changes in biofilm thickness, covered area and volume. The viable attached population of L. monocytogenes was almost unaffected by all of the enzymes here tested, being eliminated on average just the 90% of the initially attached population (around 1 Log10  cfu cm −2 reduction). Nevertheless, some of the partner species ( Escherichia coli and Staphylococcus saprophyticus ) were sometimes protected from enzymatic detachment when in dual-species biofilms, depending on the enzyme tested and the accompanying L. monocytogenes strain. CLSM images showed important changes in biofilm covered area and volume after DNase I, pronase and pectinase treatments. These results demonstrate that enzymes can greatly weaken dual-species biofilms structure. Nevertheless, it cannot be disregarded that detached cells from these treatments would still be viable. Thus, a control of cell viability after an enzymatic procedure in the food industry must be always considered before designing an efficient disinfection treatment. Highlights: Some species were protected from enzymes in dual biofilms with L. monocytogenes . Enzymes greatly affect dual-species biofilms structure and cellular integrity. They can be a good alternative for weakening dual biofilms carrying L. monocytogenes .